Comparative Analysis of Root Dentin Loss when Using Modern Mechanical Cleaning Instruments in Immature Permanent Teeth - Krasimir Hristov; Natalia Gateva; Nikolay Ishkitiev; Nikolay Ishkitiev; Liliya Doitchinova (Folia Medica, 2020)
Introduction: The full decontamination and disinfection of the root canal system is essential for the success of regenerative endodontic procedures. The current literature does not have information regarding mechanical cleaning of immature teeth with contemporary endodontic instuments.Aim: To compare the thickness and volume of the dentin removed from the roots of immature teeth after endodontic preparation using XP-endo Finisher, GentleFile Brush and a standard H-file scraping technique through micro-computed tomography.Methods: The study included 51 immature permanent molars. Endodontic access was prepared and without performing preliminary extirpation of the pulp, the teeth were divided into three groups. The first group of teeth were instrumented for two minutes with XP-endo Finisher, the second - two minutes with Gentlefile Brush, in the third group the root canals walls were scraped with a No. 40 H-file. The thickness and the volume of the removed dentin was assessed using micro-CT imaging before and after the use of the instruments.Results: There is no statistically significant difference in the mean values of thickness of dentin removed between the teeth, prepared with XP-endo finisher and Gentlefile Brush. When comparing the mean values of volume of dentin removed between the separate groups, a statistically significant difference was discovered for every compared pair with the highest volume of removed dentin in the group prepared with a hand instrument.Conclusion: The endodontic systems tested when used in immature permanent teeth remove significantly less quantity of hard dental structures compared to a hand file for scraping the root canal.